2017
DOI: 10.14738/assrj.417.3478
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming barriers of isolation in Distance Learning: Building a Collaborative Community in Learning

Abstract: The rise in popularity of distance education programmes in a rural and remote Namibia poses challenges on students that are far removed from their colleagues, tutors and even their study materials. Interaction between the student and the study materials, tutors and peers are key challenges in open and distance learning. At the same time, sparsely populated areas of the country with less network coverage pose more challenges for web-based learning that could close up the gap. Using interviews, supported by this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 13 publications
3
8
0
Order By: Relevance
“…Indeed, lack of training in the use of distance learning was one of the most often reported barriers. Other studies have also recognized the presence of similar of these barriers in post-secondary agricultural learning (Mbukusa et al, 2017). Our finding is also consistent with Irvin et al, (2010), who identified the lack of trained professionals to be a common barrier in distance learning in the United State.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, lack of training in the use of distance learning was one of the most often reported barriers. Other studies have also recognized the presence of similar of these barriers in post-secondary agricultural learning (Mbukusa et al, 2017). Our finding is also consistent with Irvin et al, (2010), who identified the lack of trained professionals to be a common barrier in distance learning in the United State.…”
Section: Discussionsupporting
confidence: 92%
“…Lastly, this study agreed with Slimi (2020) that not funding e-learning is another challenge parents may face because buying technology for e-lessons and the cost of the internet can lead to financial problems. Also, the findings of this study agreed with those of Mbukusa (2017) and Slimi (2020) in defining the lack of training as one of the biggest challenges in e-learning. Also, parents should understand technology (Bukhkalo, Ageicheva, & Komarova, 2018) however, their understanding of technology is not enough to support their children if they are unable to participate in their e-learning lessons (Slimi, 2020).…”
Section: The Challenges Facing E-learning In Omani Schoolssupporting
confidence: 90%
“…This high ratio demonstrates the heedful the Saudi parents have shown to ensure the efficacy and the successful continuity of home learning. It is evident that the Saudi parents did not face difficulty communicating with their children's teachers, which controverts with those of Grabe et al ( 2020) and Mbukusa et al (2017), where the respondents reported having difficulties connecting with the teachers.…”
Section: Table 2 Parent Challengesmentioning
confidence: 69%
“…Such a low percentage could be ascribed to the educational level of the participants. However, Other studies have recognized a contradictory result where the parents could not offer academic help to their children due to their low qualifications (Mbukusa et al, 2017;Abuhammad, 2020). Furthermore, a high percentage of Saudi parents, about 86.27%, constantly and frequently motivated their children to take part in class discussion comparatively to 3.92% and 9.80% who never or sometimes, respectively, induce their children to be active participants during online sessions.…”
Section: Table 2 Parent Challengesmentioning
confidence: 99%